2022
DOI: 10.3390/cells11132024
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D Deficiency in Mice Increases White Adipose Tissue Inflammation in Offspring

Abstract: Vitamin D is acknowledged to play an important biological and metabolic role in adipose tissue, which is also the main storage site for this vitamin. Its anti-inflammatory effect in adipocytes and adipose tissue has notably been highlighted in adult mice. This vitamin is also crucial during fetal development since maternal vitamin D deficiency is suspected to program future metabolic disorders. Based on these observations, the aim of this study was to evaluate the consequences of maternal vitamin D deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Vitamin D (VD) is a type of secosterol produced endogenously in the skin and obtained by diet, exists in two forms vitamin-D2 and -D3 and the bioactive form is 1α, 25-dihydroxyvitamin D3(1,25(OH) 2 D3, calcitriol) involved in DNA methylation, in histone modifications and in miRNAs regulation [171]. Studies in mice have shown that a deficiency of maternal VD increases WA inflammatory responses in adults [172], thus, VD intake can limit inflammation and leukocyte infiltration by decreasing miR-146a, miR-150, and miR-155 after a high fat (HF) diet supplemented with VD [173]. Additionally, combination of vitamins intake in defined doses could have Environmental Epigenetics and Obesity DOI: http://dx.doi.org/10.5772/intechopen.110507 greater benefits as epidrugs compared with single intake, since an adequate dietary of both vitamin B9 (folate) and vitamin B12 (cobalamin) may protect against metabolic imbalance [174].…”
Section: Current and Future Epidrugs Against Environmental-pollution ...mentioning
confidence: 99%
“…Vitamin D (VD) is a type of secosterol produced endogenously in the skin and obtained by diet, exists in two forms vitamin-D2 and -D3 and the bioactive form is 1α, 25-dihydroxyvitamin D3(1,25(OH) 2 D3, calcitriol) involved in DNA methylation, in histone modifications and in miRNAs regulation [171]. Studies in mice have shown that a deficiency of maternal VD increases WA inflammatory responses in adults [172], thus, VD intake can limit inflammation and leukocyte infiltration by decreasing miR-146a, miR-150, and miR-155 after a high fat (HF) diet supplemented with VD [173]. Additionally, combination of vitamins intake in defined doses could have Environmental Epigenetics and Obesity DOI: http://dx.doi.org/10.5772/intechopen.110507 greater benefits as epidrugs compared with single intake, since an adequate dietary of both vitamin B9 (folate) and vitamin B12 (cobalamin) may protect against metabolic imbalance [174].…”
Section: Current and Future Epidrugs Against Environmental-pollution ...mentioning
confidence: 99%
“…6 Under the same experimental conditions, maternal VDD coupled with a HFD induced an increase in white adipose tissue inflammation as well as increased adiposity in male offspring only, thus highlighting the sexual dimorphism in response to developmental VDD. 50 Maternal VDD is also associated with an increased risk of type 1 diabetes in the offspring. 51,52…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…6 Under the same experimental conditions, maternal VDD coupled with a HFD induced an increase in white adipose tissue inflammation as well as increased adiposity in male offspring only, thus highlighting the sexual dimorphism in response to developmental VDD. 50 Maternal VDD is also associated with an increased risk of type 1 diabetes in the offspring. 51,52 Maternal VD status also affects the epigenome of the foetus via different epigenetic mechanisms, particularly in the early stages of gestation, which can contribute to the onset and progression of diseases in adulthood.…”
Section: Vitamin D Deficiency During the Perinatal Periodmentioning
confidence: 99%
“…Female mice (15 per group) were mated with males after being assigned to one of two experimental groups based on diet: control (AIN-93G with vitamin D3, 1.0 IU g −1 ) or vitamin D-depleted (AIN-93G without vitamin D3, 0.0 IU g −1 ) for 8 weeks, as previously described. [19,20] All females were fed a control diet (AIN-93G) after delivery until the offspring were weaned. The litter size of the females was lowered to six pups.…”
Section: Animal Experimentsmentioning
confidence: 99%